Genetic predisposition to celiac disease in Kazakhstan: Potential impact on the clinical practice in Central Asia - Poddighe, Dimitri; Turganbekova, A.; Baymukasheva, Dana; Saduakas, Zhazira; Zhanzakova, Zhuldyz; Abdrakhmanova, S. (PLoS One, 2020)
Background Celiac disease (CD) is a systemic immune-mediated disorder developing in HLA genetically predisposed individuals carrying HLA-DQ2 and/or HLA-DQ8 molecules. Recent evidences supported a predominant importance of HLA-DQB1 locus and, in particular, HLA-DQB1*02 alleles. This diagnosis is poorly considered in Kazakhstan, because of the assumption that CD is not prevalent in this population. Objective To demonstrate that the genetic predisposition to CD in Kazakhstan is not negligible and is actually comparable to Western populations. Methods Through the analysis of HLA-DQ genotypes of healthy bone marrow donors from Kazakhstan’s national registry, we estimated the HLA-related genetic predisposition to CD in the country. Results We demonstrated that the frequency of CD-related HLA-DQB1 alleles and, as a consequence, of predisposed individuals to CD in Kazakhstan is significant and comparable to countries with the highest disease prevalence. Conclusion Considering the dietary style in Kazakhstan, including wheat as a staple food, these results provided a preliminary background of knowledge to expect a significant CD prevalence in Kazakhstan and Central Asia by implementing appropriate and cost-effective diagnostic strategies.
Keywords: Research Subject Categories::NATURAL SCIENCES::Biology